Inovasi Kelembagaan Unit Pelayanan Teknis Dinas Balai Rehabilitasi Terpadu Penyandang Disabilitas di Dinas Sosial Daerah Istimewa Yogyakarta - Muhammad Rasyid Prasmi; Ulung Pribadi (Universitas Muhammadiyah Yogyakarta, 2015)
The background of this study is to see that the Social Service Special Region of Yogyakarta, which is one of theagencies involved in the handling of social welfare problems in view the demands and peramsalahan social welfare areincreasingly complex, the Department of Social Welfare in answering this demand by institutional innovation by establishingnew institutional namely Technical Services Unit (UPTD) Integrated Rehabilitation Center for persons with Disabilities(BRTPD) with persons with disabilities blind, mentally disabled, physically disabled, deaf, and mute. In thisstudy, the type of research that will be used is descriptive qualitative approach. Data collection techniques used are inthe form of documentation, interviews, and observation / direct observation. The data analysis is conducted by meansof data collection, data assessment, data interpretation, and conclusion, which is adapted to the prevailing theory andrecognized, on a variable institutional innovation indicators vision and strategy, gluing basic kpetensi, strengtheninginformation and intelligence organizations, market orientation and customers, creativity and idea management, systemsand organizational structures, management ideas and also variable factors that influence institutional innovationwith indicators of internal bureaucracy, the political environment, the external environment. Results from this studyindicate that the institutional innovation UPTD Integrated Rehabilitation Center for Persons with Disabilities conductedSocial Service in outline with menggukan indicators in this study strongly support the creation of institutional innovationUPTD Integrated Rehabilitation Center for Persons with Disabilities. Factors that influence institutional innovationis internal bureaucracy that human resources are still limited in terms of quality and quantity, the political environmentis not yet fully support the budget, and the environment outside the public sector (external) that is too high expectationsof the public are not comparable with capacity owned by hall integrated rehabilitation of persons with disabilities.